The real COVID-19 pandemic dynamics in Qatar in 2021: simulations, predictions and verifications of the SIR model - Igor Nesteruk (Semina: Ciências Exatas e Tecnológicas, 2021)
The third COVID-19 pandemic wave in Qatar was simulated with the use of the generalized SIR-model and the accumulated number of cases reported by Johns Hopkins University for the period: April 25 - May 8, 2021. The results were compared with the SIR simulations performed before for the second wave and the number of laboratory-confirmed cases in the first half of 2021. Despite the mass vaccination that began in December 2020, Qatar experienced a new epidemic wave in March-April 2021. As of the end of June 2021, the positive effects of vaccination were still unclear, although the number of fully vaccinated was already approaching half the population. Additional simulations have demonstrated that many COVID-19 cases are not detected. The real accumulated number of cases in Qatar can exceed the laboratory-confirmed one more than 5 times. This fact drastically increases the probability of meeting an infectious person and the epidemic duration.